University Students' Attitudes towards the Use of YouTube in the EFL Classroom - María Victoria Fernández-Carballo (Asociación Colombiana de Profesores de Ingles, 2021)
Noticing the generally lower-than-desirable English language proficiency level with which Spanish students start university, I considered trying a different approach in which the use of a familiar application would be introduced in the classroom. The main objective of this work is to explore Primary Education degree programme students' attitudes towards the integration of YouTube in the English language classroom. To this end, 46 third-year intermediate-level students participated in the study. It adopted a mixed-method approach, using a combination of qualitative and quantitative methods. The results show that, although participants mentioned some drawbacks, they reacted positively to the use of the platform. Given these results and the benefits offered, the integration of YouTube in the foreign language classroom is highly recommended.